To Integrate Or Not: A Comparison of the English Skills of Finnish Students in Mainstream Education and Content and Language Integrated Learning - Juuti, Maria-Elena (My University, 2016)
The objective of the thesis was to study the possible linguistic differences of English of Finnish mainstream students and Finnish students following content and language integrated learning (CLIL), in terms of the given language test. The difference of test results between the test groups was further analyzed in more detail. The research was carried out by comparing the 9th grade students of the Finnish comprehensive school (the mainstream group) and CLIL students of the 9th grade of the Finnish comprehensive school (the CLIL group). The comparison was based on the national language test for the 9th grade students of the Finnish comprehensive school 2006 (A-English), produced by Sukol-Palvelu, owned by the Federation of Foreign Language Teachers in Finland SUKOL. The mainstream group of the present study consisted of 30 students, whereas the CLIL group included 27 students. Testing was carried out in spring 2007. The test results of the mainstream group (average of 64.1% out of the maximum score) were consistent with the results of the national average (63.9%). The average score of the CLIL students for the present study was 83.3% out of the maximum score. The results of the two groups in question were rather similar in the tasks measuring the skill of listening comprehension, in addition to one of the reading comprehension tasks. Moreover, a particular task with requirements of cultural and reactional skills produced results rather similar between the test groups. The differences between the results of the mainstream group and the CLIL group were most evident in three particular tasks. In general, the CLIL group performed clearly better than the mainstream group in the task measuring the knowledge of the polite conversational manners of the English-speaking world and in the tasks with requirements of lexical and structural knowledge of English. However, the writing task resulted in the most evident difference of results between the groups. In other words, the CLIL students of the present study were clearly more capable of producing English language with more varied vocabulary and more complex structures than the mainstream students. Thus, it might be argued whether the CLIL programme is to enhance the students´ performance in the productive skill of writing in particular. As a result, it might be useful to consider the possibilities of the CLIL programme in developing certain linguistic skills of the mainstream students of English as well.